Recent trends in MXene polymeric Hydrogel bionanoarchitectures and applications - Christopher Igwe Idumah (Cleaner Materials, 2022)
Recently, hydrogels (HYD) have garnered tremendous interest because of their potential uses in sensors, flexible energy storing gadgets, human@machine-interfacial systems, soft electronics and actuating machines. As a result of their inherent exhibition of hydrophilicity, metallically inclined conductivity, elevated aspect ratio, architectural disposition along with tune-able attributes, when 2-D transitionally inclined metallic carbides/nitrides or M−X are embedded within HYD systems, they give enchanting and wide settings for the fabrication of M−X oriented soft materials with tunable applicability and multifunctional properties. M−X@HYD bionanoarchitectures exceptional properties are propelled by intricate gel architectures along with gelation strategies, requiring versatile studies and engineering at the nanoscale. Nevertheless, M−X embedment within HYD can notably increment M−X stability, which regularly is an inhibiting parameter for varying M−X oriented uses. Nevertheless, through simplified modifications, M−X@HYD derivatives like aerogels, are liable to be garnered, thereby broadening their horizon. Therefore, this elucidation presents recently emerging trends in M−X@HYD architectures, multifunctional applications and enhancement of the performance of M−X−oriented gadgets. Herein, the prevailing architectures of varying M−X@HYD constructions as well as inherent gelation mechanisms along with their interlinkage propelling forces are elucidated. Their unique properties and multifunctional applications (electromagnetic interference shielding, biomedicals, energy storage/harvesting, sensing and catalysis), emanating from embedment of M−X within HYD are comprehensively and elaborately elucidated in this review paper.